2014
DOI: 10.1007/978-3-319-12160-4_18
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficacy of Solving LWE by Reduction to Unique-SVP

Abstract: Abstract. We present a study of the concrete complexity of solving instances of the unique shortest vector problem (uSVP). In particular, we study the complexity of solving the Learning with Errors (LWE) problem by reducing the Bounded-Distance Decoding (BDD) problem to uSVP and attempting to solve such instances using the 'embedding' approach. We experimentally derive a model for the success of the approach, compare to alternative methods and demonstrate that for the LWE instances considered in this work, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Lyubashevsky and Micciancio (Theorem 1 of [17]) argue that the best choice for M above is e , which is approximately √ mσ in our case. However, in our experiments M = 1 worked fine (and leads to a more powerful attack [2] in practice).…”
Section: Standard Lattice Attack On Lwementioning
confidence: 78%
“…Lyubashevsky and Micciancio (Theorem 1 of [17]) argue that the best choice for M above is e , which is approximately √ mσ in our case. However, in our experiments M = 1 worked fine (and leads to a more powerful attack [2] in practice).…”
Section: Standard Lattice Attack On Lwementioning
confidence: 78%
“…We stress that no data is publicly available on τ for smaller success probabilities. In [AFG14] it is shown that for a fixed δ 0 the optimal subdimension is m = n log q log δ0 as in Section 3.3. We may use this to determine δ 0 using the expression above (where for simplicity we assume equality).…”
Section: Reducing Bdd To Usvpmentioning
confidence: 94%
“…Albrecht, Fitzpatrick and Göpfert [AFG14] consider the complexity of solving LWE by reducing BDD to uSVP (unique Shortest Vector Problem). Formally, the γ-uSVP problem is as follows: given a lattice L such that λ 2 (L) > γλ 1 (L), find a shortest nonzero vector in L.…”
Section: Reducing Bdd To Usvpmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to solve LWE is the reduction of LWE to uSVP and the usage of an SVP solver. This so called "embedding approach" or "embedding attack" is analyzed in [AFG13]. However, still no attack has emerged that works best in all cases.…”
Section: Security Evaluation Of Lattice-based Cryptographymentioning
confidence: 99%